Peramalan Kredit Modal Kerja di Indonesia Menggunakan Brown's Double Exponential Smoothing dengan Optimasi Pencarian Dikotomis - Yustiani, Iis; Wahyuningsih, Sri; Siringoringo, Meiliyani (Program Studi Statistika FMIPA Universitas Mulawarman, 2022)
Brown's Double Exponential Smoothing (DES) method is a forecasting method with the smoothing process carried out twice. DES Brown has one parameter to define, and it is usually done in a trial and error manner. Another way to determine value parameters more quickly and precisely is to use optimization methods. In this study, forecasting of working capital credit in Indonesia using DES Brown for the period May to July 2022 was carried out with dichotomous search optimization. The results showed that the results of forecasting for working capital loans showed a decrease in May then increased in June and July with a very good forecasting accuracy, namely the MAPE value of 1.480768%.